2021
DOI: 10.1007/s11096-021-01251-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantity and quality profiles of antibiotics pre, on, and post surgery in a hospital setting

Abstract: Background Providing proper antibiotics is undoubtedly crucial to prevent infections during surgery. Objective This study set out to evaluate the medication administration in antibiotic prophylaxis using both quantitative and qualitative methods. Setting The study employed a retrospective design and observed patients who underwent surgical procedures during hospitalization at a private hospital in Indonesia within the period of January-June 2019. Methods The data obtained were evaluated quantitatively and qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…A total of 20 reports (5 193 626 patients) reported data on antibiotic consumption. 1938 Most of the studies were conducted in hospital settings (16 reports, 76.2%), in Java (14 reports, 66.7%), and between 2016-2021 (17 reports, 81.0%; Table S4 ). The pooled estimate of overall antibiotic consumption was 110.1 DDD/100 patient-days (95% confidence interval [CI] 98.5-121.6; I 2 =100%; Figure S1 ), with ceftriaxone being the most consumed antibiotic (60.2 DDD/100 patient-days [95%CI 34.2-86.1]), followed by ampicillin (28.0 DDD/100 patient-days [95%CI 0.00-82.8]) and levofloxacin (21.4 DDD/100 patient-days [95%CI 15.4-27.3]; Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 20 reports (5 193 626 patients) reported data on antibiotic consumption. 1938 Most of the studies were conducted in hospital settings (16 reports, 76.2%), in Java (14 reports, 66.7%), and between 2016-2021 (17 reports, 81.0%; Table S4 ). The pooled estimate of overall antibiotic consumption was 110.1 DDD/100 patient-days (95% confidence interval [CI] 98.5-121.6; I 2 =100%; Figure S1 ), with ceftriaxone being the most consumed antibiotic (60.2 DDD/100 patient-days [95%CI 34.2-86.1]), followed by ampicillin (28.0 DDD/100 patient-days [95%CI 0.00-82.8]) and levofloxacin (21.4 DDD/100 patient-days [95%CI 15.4-27.3]; Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 20 reports (5 193 626 patients) reported data on antibiotic consumption. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Most of the studies were conducted in hospital settings (16 reports, 76.2%), in Java (14 reports, 66.7%), and between 2016-2021 (17 reports, 81.0%; Table S4). The pooled estimate of overall antibiotic…”
Section: Antibiotic Consumptionmentioning
confidence: 99%
“…8,9 However, unnecessary or suboptimal prescriptions of antimicrobial prophylaxis is a common phenomenon worldwide, including excessive use of antibiotics, inappropriate selection or dosages, prolonged duration or incorrect timing of first dose, which may result in antibiotic resistance and higher healthcare costs. 10 Quality control circle (QCC) is a process management and problem-solving technique founded in 1962 by Dr Kaoru Ishikawa of Japan, which is viewed as a powerful tool to solve the problems in work and improve the complex work flow by the joint efforts of all members composed of staff from the same or similar complementary workplaces. 11 Until 2001, QCC activities was introduced to healthcare industry in China, and numerous studies have revealed that the application of QCC could effectively raise the quality of medical service and ensure the safety of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although perioperative antimicrobial prophylaxis (PAP) guidelines across a wide array of surgical procedures have been proposed [8,9]. Still, suboptional use of antimicrobial for surgical prophylaxis is a common phenomenon worldwide, such as without indication, inappropriate selection or dosing of antimicrobial agents, prolonged duration of antimicrobial agents, incorrect timing of prophylaxis, which may result in AMR and higher healthcare costs [10].…”
Section: Introductionmentioning
confidence: 99%